In situ microbial viability assessment of key foodborne contaminants during hydration-dehydration cycles in Edible Drupes - Sannamuri, Hari (Universitas 'Aisyiyah Yogyakarta, 2025)
Ensuring the microbiological safety of low-moisture foods, particularly tree nuts, remains a critical challenge in food processing. This study quantitatively investigated the kinetic behavior and persistence of prominent foodborne pathogens (Salmonella spp., Listeria monocytogenes, and Shiga toxin-producing Escherichia coli) within Prunus dulcis kernels subjected to typical industrial hydration (soaking) and subsequent dehydration (drying) regimes. Artificially contaminated samples were processed under controlled environmental conditions, and microbial populations were enumerated at discrete time points to elucidate growth potential and survival dynamics. Results indicated significant variability in pathogen response to moisture management interventions, with specific critical control points identified where microbial proliferation or enhanced resistance could occur. These findings provide crucial data for enhancing process validation protocols and refining risk mitigation strategies within the tree nut industry, contributing to improved public health outcomes by characterizing pathogen fate during posthar-vest processing.